TorsinA folding and N-linked glycosylation are sensitive to redox homeostasis - Honer, Jonas (2021)
The Endoplasmic Reticulum (ER) is responsible for the folding and post-translational modification of secretory proteins, as well as for triaging misfolded proteins. During folding, there is a complex yet only partially understood interplay between disulfide bond formation, which is an enzyme catalyzed event in the oxidizing environment of the ER, along with other post-translational modifications (PTMs) and chaperone-supported protein folding. Here, we used the glycoprotein torsinA as a model substrate to explore the impact of ER redox homeostasis on PTMs and protein biogenesis. TorsinA is a AAA+ ATPase with unusual oligomeric properties and controversial functions. The deletion of a C-terminal glutamic acid residue (∆E) is associated with the development of Early-Onset Torsion Dystonia, a severe movement disorder. TorsinA differs from other AAA+ ATPases since it is an ER resident, and as a result of its entry into the ER torsinA contains two N-linked glycans and at least one disulfide bond. The role of these PTMs on torsinA biogenesis and function and the identity of the enzymes that catalyze them are poorly defined. Using a yeast torsinA expression system, we demonstrate that a specific protein disulfide isomerase, Pdi1, affects the folding and N-linked glycosylation of torsinA and torsinA∆E in a redox-dependent manner, suggesting that the acquisition of early torsinA folding intermediates is sensitive to perturbed interactions between Cys residues and the quality control machinery. We also highlight the role of specific Cys residues during torsinA biogenesis and demonstrate that torsinA∆E is more sensitive than torsinA when these Cys residues are mutated.